A 15-year consolidated overview of data in over 6000 patients from the Transthyretin Amyloidosis Outcomes Survey (THAOS) - Gentile, Luca; Coelho, Teresa; Dispenzieri, Angela; Conceição, Isabel; Waddington-Cruz, Márcia; Kristen, Arnt; Wixner, Jonas; Diemberger, Igor; Gonzalez-Moreno, Juan; Cariou, Eve; Maurer, Mathew S.; Planté-Bordeneuve, Violaine; et al. (Orphanet journal of rare diseases, 2023)
Transthyretin amyloidosis (ATTR amyloidosis) is a progressive, multisystemic, life-threatening disease resulting from the deposition of variant or wild-type (ATTRwt amyloidosis) transthyretin amyloid fibrils in various tissues and organs.